2012
DOI: 10.1111/j.1365-2826.2011.02273.x
|View full text |Cite
|
Sign up to set email alerts
|

Region‐Specific Changes in Transient Receptor Potential Vanilloid Channel Expression in the Vasopressin Magnocellular System in Hepatic Cirrhosis‐Induced Hyponatraemia

Abstract: The purpose of this study was to measure the expression of transient receptor potential (TRP) channels in the magnocellular neurons of the paraventricular (PVN) and supraoptic nucleus (SON) in an animal model of hepatic cirrhosis associated with inappropriate vasopressin (AVP) release. In these studies we used chronic bile duct ligation (BDL) in the rat, a commonly used model of hepatic cirrhosis, associated with elevated plasma AVP. This study tested the hypothesis that changes in TRPV channel expression may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 56 publications
7
31
2
Order By: Relevance
“…In a previous study, experimental cirrhosis in the rat was not associated with increased oxytocin gene expression in the hypothalamus, although the study used a different model of cirrhosis (33). We did not observe a significant increase in the numbers of oxytocin-positive neurons following BDL in the current study or a previous publication (41). However, we did observe a significant increase in ⌬FosB and oxytocin double labeling in the SON of BDL rats.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In a previous study, experimental cirrhosis in the rat was not associated with increased oxytocin gene expression in the hypothalamus, although the study used a different model of cirrhosis (33). We did not observe a significant increase in the numbers of oxytocin-positive neurons following BDL in the current study or a previous publication (41). However, we did observe a significant increase in ⌬FosB and oxytocin double labeling in the SON of BDL rats.…”
Section: Discussioncontrasting
confidence: 75%
“…It is also possible that the downstream targets of ⌬FosB are involved in other cellular processes necessary for sustained activation and/or hormone release. It has previously been reported that BDL is associated with significant changes in TRPV2 and TRPV4 expression in SON neurons (11,41). However, few studies have characterized the transcriptional regulation of these channels (13,26,30), and therefore it is not known if their expression is regulated by AP-1 transcription factors.…”
Section: Discussionmentioning
confidence: 98%
“…This is in good agreement with the previous data that Trpv1-4 mRNAs were detected in rat SON neurones that were laser-captured using an anti-AVP antibody [29]. These results are also consistent with our experiments on SON neurones isolated from transgenic rats that revealed that the mannitol response was observed solely in AVP but not in OT neurones.…”
Section: Specific Expression Of Trpv1 In Avp Neuronessupporting
confidence: 95%
“…It has been demonstrated previously that TRPV1 is expressed in AVP neurones in rat SON [29]. In the present study, we have also found that the distribution of TRPV1 immunoreactivity was confined to the ventral region where most AVP-immunoreactive neurones dwell.…”
Section: [Ca 2+ ] I Responses In Son Neurones Isolated From Transgenisupporting
confidence: 79%
“…The failure to observe concurrent increases in c-fos and vasopressin hnRNA expression led the authors to suggest the induction of these genes following acute osmotic stimulation likely involves different mechanisms. It is possible that other downstream targets of ⌬FosB, such as transient receptor potential vanilloid channels (14,50) or changes in synaptic function (47,69) are involved in the sustained activation and/or hormone release that results in dilutional hyponatremia.…”
Section: R602mentioning
confidence: 98%